2021
DOI: 10.1001/jamanetworkopen.2021.17049
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19–Related Immigration Concerns Among Latinx Immigrants in the US

Abstract: IMPORTANCE Despite the contentious immigration environment and disproportionate rates of COVID-19 infection among Latinx individuals in the US, immigrants' concerns about engaging in COVID-19-related testing, treatment, and contact tracing have been largely unexplored. OBJECTIVE To examine the proportions of Latinx immigrants who endorse statements about the potential negative immigration ramifications of seeking and using COVID-19-related testing and treatment services and engaging in contact tracing. DESIGN,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…Will it go to immigration?” People in the community were unsure if or how receiving a COVID-19 vaccine would impact their immigration status. Many undocumented Latino individuals fear accessing services such as COVID-19 testing, contact tracing, and vaccination because they are concerned with the potential negative immigration ramifications of using these services ( Galletly et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Will it go to immigration?” People in the community were unsure if or how receiving a COVID-19 vaccine would impact their immigration status. Many undocumented Latino individuals fear accessing services such as COVID-19 testing, contact tracing, and vaccination because they are concerned with the potential negative immigration ramifications of using these services ( Galletly et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, approximately half of respondents in our sample identified lack of health insurance/health card as a major barrier to COVID-19 vaccination. Although concerns about immigration have been shown to dampen healthcare utilisation for COVID-19 services among undocumented migrants,54 we did not specifically ask whether worries about immigration repercussions impacted demand. In our study, public hospitals or clinics were identified as preferred sites for vaccination among those intending to get vaccinated, but we did not collect information about trust in public institutions among vaccine-hesitant participants.…”
Section: Discussionmentioning
confidence: 99%
“…For migrants in particular, the collection of personal data for public health purposes, raises concerns for their privacy and safety. Immigrants have expressed concerns accessing COVID-19 related programs due to the fear of exposing their immigration status [44,45]. Examples of extracting personal data from mobile phones stem into migration and mobility management practices, as it is becoming common among authorities to use personal electronic devices as a verification tool, gaining access to call data, text messages, location history and more [26].…”
Section: Entry: Increased (Bio)surveillancementioning
confidence: 99%